Efektivitas Program Peningkatan Kualitas Guru Profesional sebagai Studi Kasus pada MAN 1 Cibinong Kab. Bogor - Maman Saepulloh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the effectiveness of professional development programs for teachers in improving teaching quality at MAN 1 Cibinong Kab. Bogor. Through a case study method, this research analyzes how training, supervision, and evaluation contribute to the enhancement of teacher competence and performance. Data were collected through interviews, observations, and school documentation related to professional development processes. The findings reveal that a structured approach in training and supervision significantly motivates teachers to improve their skills, while challenges such as time allocation and resource limitations must also be addressed. This study recommends sustainable strategies for improving teacher professional development programs.